2020
DOI: 10.1111/anae.15294
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of reporting quality for anaesthetic interventions in randomised controlled trials

Abstract: Interventions from randomised controlled trials can only be replicated if they are reported in sufficient detail. The results of trials can only be confidently interpreted if the delivery of the intervention was systematic and the protocol adhered to. We systematically reviewed trials of anaesthetic interventions published in 12 journals from January 2016 to September 2019. We assessed the detail with which interventions were reported, using the Consolidated Standards of Reporting Trials statement for non-phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Fourth, we did not assess the degree to which manuscripts adhered to the reporting guideline recommendations when a reporting guideline was used; this assessment was beyond the scope of this study. However, several publications show that adherence to guidelines such as PRISMA and CONSORT has not been optimal in diverse areas, including rheumatology, 12 cardiovascular medicine, 18 pediatric urology, 19 occupational health, 20 obstetrics, 21 anesthesiology, 22 emergency medicine, 23 internal medicine, 24 head and neck cancer, 25 and otorhinolaryngology. 26 Finally, readers should be aware that the use of these reporting guidelines should not necessarily be equated to a high-quality presentation of study findings, but to ensuring the manuscript contains the necessary elements to properly evaluate the scientific endeavor and enhance reproducibility in science.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we did not assess the degree to which manuscripts adhered to the reporting guideline recommendations when a reporting guideline was used; this assessment was beyond the scope of this study. However, several publications show that adherence to guidelines such as PRISMA and CONSORT has not been optimal in diverse areas, including rheumatology, 12 cardiovascular medicine, 18 pediatric urology, 19 occupational health, 20 obstetrics, 21 anesthesiology, 22 emergency medicine, 23 internal medicine, 24 head and neck cancer, 25 and otorhinolaryngology. 26 Finally, readers should be aware that the use of these reporting guidelines should not necessarily be equated to a high-quality presentation of study findings, but to ensuring the manuscript contains the necessary elements to properly evaluate the scientific endeavor and enhance reproducibility in science.…”
Section: Discussionmentioning
confidence: 99%
“…Formal statistical comparison will not be undertaken because the overall aim of this review is to summarise reporting standards and not to analyse specific trial results. The same approach has been taken in other published systematic reviews that have analysed reporting standards in other research fields [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent analysis of the description of complex interventions in surgery and anaesthesia RCTs demonstrated poor reporting standards and poor adherence to CONSORT-NPT guidance. These studies suggested that the current guidance might not be adequate for RCTs involving complex interventions and that more comprehensive and specific frameworks for intervention descriptions should be developed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication has shown that protocol adherence is only adequately reported in 12% of publications in anesthesia and perioperative medicine. 6 Provision of information about protocol adherence is fundamental for appropriate interpretation of results. Fortunately, Wang et al 5 provided this information; 8 summary statistics of pEEG adherence are reported.…”
mentioning
confidence: 99%